Economic consequence of social and environmental concern in Islamic bank – Do COVID-19 pandemic matter? - Asrori; Hasan Mukhibad; Ahmad Nurkhin (Cogent Business & Management, 2023)
Islamic banks should care about social and environmental issues. However, the economic consequence of social and environmental concerns is still being debated. This study aims to prove the role of economic consequences of social and environmental concerns and market competition on financial performance. Based on the system-oriented view, the entity is assumed to be influenced by, and in turn, to have an influence upon, the society in which it operates, including the crisis due to the COVID-19 pandemic, which had an impact on bank operations. Based on this argument, this research aims to examine the role of the COVID-19 pandemic in the relationship between social and environmental concerns and market competition on financial performance. This study uses hand-collected data on the annual reports of 14 full-flagged Islamic banks (IBs) in Indonesia between 2009 and 2021. Data were analyzed using GLS regressions with robust standard errors. This study showed that social and environmental concerns and market competition did not affect financial performance. Therefore, the COVID-19 pandemic plays a major role in the extent to which social and environmental concerns affect financial performance. The findings suggest that directors should increase the effectiveness of the distribution of social funds to improve financial performance.
Keywords: 650; Covid-19 pandemic; economic consequence; environmental concern; qardul hasan funds; System-oriented view